Analysis of Learning Difficulties About Introduction to Accounting And Finance of Worksheet Material Learning - Martodiryo, Suratno; Rizky, M.; Hadi, Rizali (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The results of the analysis test can be used as a means to know the students' learning difficulties and as a guide to know how to overcome such difficulties. The purpose of this study is to identify and know the causes of learning difficulties on accounting worksheet materials. In analyzing the data presented the difficulty of learning accounting work sheet material based on the cognitive domain. The results showed that students had difficulty working on the worksheet on the dimensions of remembering i.e : "Writing corporate identity and period of worksheet", Categorization and account coding", and on the dimensions of understanding i.e : "Write the code of the newly opened account", and on the dimensions of applying i.e : "Lacking careful when posting post balance and adjusting journal", "Preparation of balance sheet after adjusted", and on analyzing dimensions: "Specifying real account and nominal account", and on evaluating dimensions i.e : "Determine the profit/loss company," and on the dimensions of creating difficulties caused by difficulties in other dimensions, while the way to overcome learning difficulties accounting worksheet material learning is to continue to practice in working worksheet and often ask to friends and teachers if there is a not understood.